1996
DOI: 10.1021/es960317s
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Dilute Sedimentary Soot Phase:  Implications for PAH Speciation and Bioavailability

Abstract: Existing field data indicate that soot may significantly affect the environmental speciation of polycyclic aromatic hydrocarbons (PAHs). To expand hydrophobic partition models to include soot partitioning, we need to quantify f sc , the soot fraction of the solid matrix, and K sc , the sootcarbon-normalized partition coefficient. To this end, we have developed a method that allows quantification of soot carbon in dilute and complex sedimentary matrices. Nonsoot organic carbon is removed by thermal oxidation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
916
2
8

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 910 publications
(968 citation statements)
references
References 45 publications
(92 reference statements)
42
916
2
8
Order By: Relevance
“…Researchers observed that heterogeneity in naturally occurring carbonaceous materials (CMs) caused sorption processes of hydrophobic organic compounds (HOCs) in sediments to occur as a combination of absorption into amorphous organic matter and adsorption onto condensed forms of CMs such as black carbon (BC), coal, and kerogen, collectively termed "carbonaceous geosorbents" (CG) (Allen-King et al 2002;Cornelissen et al 2005). Many studies reported that adsorption of PAHs onto CG can greatly affect their bioavailability and toxicity as "sequestration" of PAHs in sediments often takes place (Gustafsson et al 1997;Luthy et al 1997;Nam et al 1998;Rockne et al 2002;Shor et al 2003;Abu and Steve 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers observed that heterogeneity in naturally occurring carbonaceous materials (CMs) caused sorption processes of hydrophobic organic compounds (HOCs) in sediments to occur as a combination of absorption into amorphous organic matter and adsorption onto condensed forms of CMs such as black carbon (BC), coal, and kerogen, collectively termed "carbonaceous geosorbents" (CG) (Allen-King et al 2002;Cornelissen et al 2005). Many studies reported that adsorption of PAHs onto CG can greatly affect their bioavailability and toxicity as "sequestration" of PAHs in sediments often takes place (Gustafsson et al 1997;Luthy et al 1997;Nam et al 1998;Rockne et al 2002;Shor et al 2003;Abu and Steve 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The sequestration of DDT and HCB is of considerable interest because of its effect on bioavailability and the risk-assessment paradigms used to guide management and cleanup of contaminated sites and soil. The processes of HOCs sequestration in soil are thought to be driven by partitioning into the soil organic matter (SOM) (Gustafsson et al, 1997;Cornelissen et al, 2005) and diffusing into soil micropores (Farrell et al, 1999). In soil with greater than 0.1% organic carbon content, partitioning into SOM has been found to be the dominant process (Chiou et al, 2000;Kang and Xing, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Sediment TOC and BC were determined in triplicate, using the chemothermal oxidation method (CTO375) as described by Gustaffson et al [16]. In this method, amorphous organic carbon is removed by thermal oxidation at 3758C followed by addition of HCl to remove possible carbonate residues.…”
Section: Chemical Analysismentioning
confidence: 99%
“…Recently, Kupryianchyk et al [15] showed how limitations in AC performance can be quantified based on organic carbon and BC content. Refractory phases such as BC and weathered oil might significantly limit desorption of HOCs to AC [16,17]. However, a substantial fraction of HOCs is known to be associated with light-density organic carbon [18] composed of humic/fulvic substances, lignin, and plant debris or mineral particles [19].…”
Section: Introductionmentioning
confidence: 99%